Roma and Bureaucrats: A Field Experiment on Ethnic and Socioeconomic Discrimination - Stepan Mikula; Josef Montag (Institute of Labor Economics (IZA), 2023)
This paper tests for discriminatory treatment of the Roma minority by public officials in the Czech Republic at the stage of initial contact preceding a potential application for unemployment benefit. Our correspondence experiment facilitates testing for the presence of each of two intertwined drivers of discrimination: ethnic animus and socioeconomic status prejudice. We find substantial evidence for the presence of discrimination based on both of these sources. Since Roma tend to have lower socioeconomic status, the two sources of discrimination compound for them.
Keywords: J15; D73; H55; 330; discrimination; Roma; ethnicity; socioeconomic status; public services; social security; field experiment